Perspektif Hukum Joint Venture in Foreign Direct Investment Indonesia-Korea Selatan dalam Industri Baterai Electric Vehicle (EV) Oleh PT HLI Green Power - Khairunnisa, Yubistika (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The global shift towards Electric Vehicles (EV) opens up strategic opportunities for Indonesia to leverage its rich nickel resources in the EV battery industry. This study examines the legal aspects of a joint venture between Indonesia and South Korea through PT HLI Green Power as a form of Foreign Direct Investment (FDI) in the development of the electric vehicle battery industry in Indonesia based on comprehensive legal aspects or relevant legal regulations, including UU No. 25 Tahun 2007 tentang Penanaman Modal, UU No. 40 Tahun 2007 tentang Perseroan Terbatas, UU No. 30 Tahun 2009 tentang Ketenagalistrikan, and other supporting regulations. The results of the study show that the HLI Green Power joint venture is an implementation of strategic collaboration between Hyundai Motor Group, LG Energy Solution, and Indonesia Battery Corporation (IBC). However, there are also challenges in the form of policy uncertainty, trade disputes with the European Union at the WTO, limited charging infrastructure, high costs of electric vehicles, the dominance of foreign investors, and limited local human resource capacity. This study concludes that the success of the joint venture requires consistent government policies, strengthened technology transfer mechanisms, more favorable profit-sharing negotiations, and the development of local human resource capacity to maximize added value for the national economy.